1989
DOI: 10.1073/pnas.86.5.1495
|View full text |Cite
|
Sign up to set email alerts
|

rev protein of human immunodeficiency virus type 1 affects the stability and transport of the viral mRNA.

Abstract: Communicated by Fotis C. Kafatos, December 6, 1988 (received for review October 6, 1988) ABSTRACT rev (trs/art) is an essential human immunodeficiency virus type 1 (HIV-1) regulatory protein. rev increases the levels of the gag-and env-producing mRNAs via a cis-acting element in the env region of HIV-1, named revresponsive element. Our results show that rev increases the stability of the unspliced viral mRNA, while it does not affect the stability of the multiply spliced viral mRNAs that do not contain the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

35
577
3
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 584 publications
(617 citation statements)
references
References 22 publications
(25 reference statements)
35
577
3
1
Order By: Relevance
“…This is consistent with our earlier results which demonstrated that the human immunode®ency type 1 (HIV-1) Rev/RRE regulatory axis could overcome the inhibitory e ect of the h1ARE . The HIV-1 Rev protein binds to its target RNA element in the nucleus and acts by promoting export of nuclear mRNAs (Emerman et al, 1989;Felber et al, 1989;HammarskjoÈ ld et al, 1989;Malim et al, 1989) through an alternative, productive route (Bogerd et al, 1995;Fisher et al, 1995;Fritz et al, 1995), thereby presumably preventing the h1ARE from interacting with nuclear proteins that mediate inhibition as the mRNA enters the cytoplasm. Recent reports have described the identi®cation of an RNaseE like activity in mammalian cells and have shown that partially puri®ed mammalian RNaseE cleaves AUUUA containing RNAs in vitro (Wennborg et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with our earlier results which demonstrated that the human immunode®ency type 1 (HIV-1) Rev/RRE regulatory axis could overcome the inhibitory e ect of the h1ARE . The HIV-1 Rev protein binds to its target RNA element in the nucleus and acts by promoting export of nuclear mRNAs (Emerman et al, 1989;Felber et al, 1989;HammarskjoÈ ld et al, 1989;Malim et al, 1989) through an alternative, productive route (Bogerd et al, 1995;Fisher et al, 1995;Fritz et al, 1995), thereby presumably preventing the h1ARE from interacting with nuclear proteins that mediate inhibition as the mRNA enters the cytoplasm. Recent reports have described the identi®cation of an RNaseE like activity in mammalian cells and have shown that partially puri®ed mammalian RNaseE cleaves AUUUA containing RNAs in vitro (Wennborg et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The major discrepancy concerns the presenee of PAB II in the nucleolus, in wh ich poly(A) has not been found [30]. Other nuclear RNA bin ding proteins involved in mRN A metabolism have been detected in the nucleolus as weil, even though no nucleolar hmction of these proteins is known [31,32]. Nonspecific binding of an abundant protein to ribosomal RNA (see above) might be an explanation.…”
Section: Resul Ts and Discussionmentioning
confidence: 99%
“…26 Rev also increases RNA stability and translation. 27 In contrast, the constitutive transport element (CTE) of Mason-Pfizer monkey virus mediates the export of unspliced RNA through the cellular RNA export factor Tap. 28 We hypothesized that the export of partially doublestranded genomic bidirectional vector RNA depends on Rev's function to overcome nuclear quality control restrictions.…”
Section: Introductionmentioning
confidence: 99%